Effect of 3 Single Doses of Trazodone on QTc Interval in Healthy Subjects. (2nd June 2020) - Tellone, Valeria; Rosignoli, Maria Teresa; Picollo, Rossella; Dragone, Patrizia; Del Vecchio, Alessandra; Comandini, Alessandro; Radicioni, Milko; Leuratti, Chiara; Calisti, Fabrizio
Abstract: This study evaluated the effect of 3 doses of a trazodone hydrochloride 6% oral drops solution on the QT interval of healthy volunteers. Subjects were randomly assigned to receive a single dose of trazodone 20 mg, 60 mg, and 140 mg, moxifloxacin 400 mg, and trazodone‐matched placebo in 5 periods separated by 7‐day washouts, according to a double‐blind, crossover study design. Subjects were monitored continuously, and triplicate ECGs were extracted from baseline (predose) until 24 hours postdose. Blood samples for trazodone and moxifloxacin analyses were collected at the same time points. The concentration‐QTc relationship assessed on placebo‐adjusted change from baseline for Fridericia‐corrected QT (ΔΔQTcF) was the primary end point. ΔΔQTcF values of 4.5, 12.3, and 19.8 ms for the 20‐, 60‐, and 140‐mg doses were observed at the corresponding trazodone peak plasma concentrations. The upper bound of the 90%CI exceeded 10 ms for the 60‐ and the 140‐mg doses. Time‐matched analysis results were in line with these findings. No significant trazodone effect on heart rate or PR or QRS intervals and no clinically significant new morphological changes were present. In this moxifloxacin‐validated ECG trial, trazodone had a modest, dose‐dependent effect on cardiac repolarization, with no QTc prolongation observed with the 20‐mg dose and an effect exceeding the values set in E14 guideline with the 60‐ and 140‐mg doses. The effect on cardiac repolarization is unlikely to represent a clinical risk for ventricular proarrhythmia, but caution should be used with concomitant use of other medications that prolong QT or increase trazodone exposure.